Positivity violation for the lattice Landau gluon propagator - Cucchieri, Attilio; Mendes, Tereza; Taurines, Andre R. [UNESP] (American Physical Society (APS), 2005)
We present explicit numerical evidence of reflection-positivity violation for the lattice Landau gluon propagator in three-dimensional pure SU(2) gauge theory. We use data obtained at very large lattice volumes (V = 803, 1403) and for three different lattice couplings in the scaling region (β = 4.2, 5.0, 6.0). In particular, we observe a clear oscillatory pattern in the real-space propagator C(t). We also verify that the (real-space) data show good scaling in the range t ε [0, 3]fm and can be fitted using a Gribov-like form. The violation of positivity is in contradiction with a stable-particle interpretation of the associated field theory and may be viewed as a manifestation of confinement. © 2005 The American Physical Society.